Constructing the Classical Past: the Role of Landscape in Christopher Wordsworth's Greece. (7th January 2022) - Hollis, Dawn L
Abstract: This article examines the works of Christopher Wordsworth (1807–85), who has hitherto been neglected as an important and intriguing figure in the history of travel writing on Greece. His texts, which invite readers to 'view' the country from mountain-tops and to imagine its caves and quarries filled with ancient figures, highlight the importance of landscape as a frame for studying classical reception. Wordsworth 'received' ancient Greece through its visible, modern landscape in three ways: through a sense of the landscape as a container for memory, through the use of specific landscapes as springboard for 'flights of fancy' enabling a vivid engagement with the classical past, and as a tool for better interpreting and understanding the history and literature of the ancient Mediterranean. Christopher Wordsworth constructed a vision of ancient Greece for his readers through his description of the nineteenth-century landscape. As such he offers an important reminder to consider the role played by the embodied experience of space and place in analysing acts of classical reception.